Design of dual-band and low-profile SIW cavitybacked slot antenna for 5G applications - Kumar A.; Khan A.; Singh A.K. (My University, 2025)
In this paper, the design of dual-band and lowprofile SIW cavity-backed slot antenna operating at K-band and Ka-band has been proposed. The dual-band antenna consists of the SIW cavity with two parallel slots which are etched on the ground plane of the conductor. In order to obtain dual-band, higher-order hybrid modes are tuned and combined to form the second band of the proposed antenna with a wider bandwidth. For dual-band antenna, fractional bandwidth of 5.26% and 6.15% are achieved with the maximum gain of 5.45 dBi and 6.15 dBi at 24.7 GHz and 27.8 GHz, respectively. In terms of antenna performances including reflection coefficient, bandwidth, gain, and radiation pattern, a cavity-backed antenna using via-hole along with the slot has been proposed. Via-hole establishes a connection between the top and bottom surfaces of the cavity creating a new path for the current to flow by shortening the effective length of the slot. The results show that the bandwidth of 4.2 GHz (15.32%) ranging from 25.3 GHz - 29.5 GHz, a gain of 7.8 dBi and 9.2 dBi have been achieved at 25.9 GHz and 28.8 GHz respectively. The overall volumetric dimension of both the proposed design including feedline is 20 mm x 14 mm x 0.508 mm. © 2021 River Publishers. All rights reserved.